Experimental and numerical study on real-time early warning of secondary collapse in semi-ruined RC frame structures under aftershocks - Defeng Xu; Feifei Sun; Yue Liu; Jixin Wen (Bulletin of Earthquake Engineering, 2026)

Development of a Sensitive Real‐Time PCR Method for Detection of Carp Oedema Virus - Huilin He; Ruixue Feng; Siyi Guo; Bing Han; Jinshan Huang; Xu Lin; Jiyuan Yin; Defeng Zhang; Min Liu; Wen Shi (Journal of Fish Diseases, 2026)
Carp oedema virus disease (CEVD), caused by the carp oedema virus (CEV), results in significant economic losses to the common carp and koi aquaculture industry. The CEVD symptoms resemble those of koi herpesvirus (KHV) and include lethargy, swollen gills, sunken eyes, and skin haemorrhages. Consequently, the development of efficient detection methods is imperative for the prevention and diagnosis of CEVD. In this study, we developed a quantitative real‐time PCR assay for the sensitive detection of CEV infection. Specific primers were designed based on a highly conserved region within the CEV p4a gene. The assay exhibited a sensitivity that was 100‐fold greater than that of the conventional PCR technique, with high specificity, and no observed cross‐reactivity with infectious haematopoietic necrosis virus (IHNV), infectious pancreatic necrosis virus (IPNV), spring viremia of carp virus (SVCV), salmonid alphavirus (SAV), or KHV. Inter‐ and intra‐assay experiments also confirmed the method's high repeatability. In a clinical setting, it showed higher sensitivity compared to the diagnostic methods for CEVD developed by the Center for Environment, Fisheries and Aquaculture Science (CEFAS), while also significantly reducing detection costs. Consequently, the established assay could provide robust technical support for the clinical diagnosis and epidemiological investigation of CEVD.

Baicalin attenuates aflatoxin B1-induced hepatotoxicity via suppressing c-Jun-N-terminal kinase-mediated cell apoptosis - Defeng Wen; Jie Zhang; Hualin Zhou; Yinsheng Qiu; Pu Guo; Qirong Lu; Jianglin Xiong (Mycotoxin Research, 2024)

Coxsackievirus and adenovirus receptor inhibits tilapia lake virus infection via binding to viral segment 8 and 10 encoded protein - Jing Wen; Zishan Ke; Yingying Wang; Yingying Li; Defeng Zhang; Xubing Mo; Jiyuan Yin; Cunbin Shi; Wenli Zhou; Shucheng Zheng; Qing Wang (Fish & Shellfish Immunology, 2024)

Baicalin attenuates lipopolysaccharide-induced intestinal inflammatory injury via suppressing PARP1-mediated NF-κB and NLRP3 signalling pathway - Qirong Lu; Nan Wang; Defeng Wen; Pu Guo; Yu Liu; Shulin Fu; Chun Ye; Zhongyuan Wu; Yinsheng Qiu (Toxicon, 2024)

Integrating network pharmacology and experimental validation to explore the mechanisms of luteolin in alleviating fumonisin B1–induced intestinal inflammatory injury - Defeng Wen; Wantong Han; Quan Chen; Guanhui Qi; Mengling Gao; Pu Guo; Yu Liu; Zhongyuan Wu; Shulin Fu; Qirong Lu; Yinsheng Qiu (Toxicon, 2024)

Fully automatic and nonparametric quantification of adipose tissue in fat–water separation MR imaging - Defeng Wang; Lin Shi; Winnie C. W. Chu; Miao Hu; Brian Tomlinson; Wen-Hua Huang; Tianfu Wang; Pheng Ann Heng; David K. W. Yeung; Anil T. Ahuja (Medical & Biological Engineering & Computing, 2015)